2003
DOI: 10.1002/cncr.11642
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of invasive breast carcinoma followed by delayed surgical excision

Abstract: Mycophenolic acid (MPA) specifically inhibits inosine‐5′‐monophosphate dehydrogenase, the first committed step toward GMP biosynthesis. In its morpholinoethyl ester pro‐drug form it is one of the most promising immunosuppressive drugs recently developed. The aim of the present study was to investigate the in vitro effects of MPA, at concentrations readily attainable during immunosuppressive therapy, on 3 human neuroblastoma cell lines (LAN5, SHEP and IMR32). Mycophenolic acid (0.1–10 μM) caused a decrease of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(141 citation statements)
references
References 51 publications
3
132
0
3
Order By: Relevance
“…Since the first report in 1999, only a few studies have been published on RFA for breast cancer treatment and all focused on US-guided RFA (5,(7)(8)(9)(10)(11)18). The largest study to date is published by Izzo et al (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first report in 1999, only a few studies have been published on RFA for breast cancer treatment and all focused on US-guided RFA (5,(7)(8)(9)(10)(11)18). The largest study to date is published by Izzo et al (9).…”
Section: Discussionmentioning
confidence: 99%
“…The experience with RFA in patients with breast carcinoma is still in the early stages of development. All previously reported studies assessing the accuracy of RFA of breast tumors used ultrasound (US) to guide the ablation probe (7)(8)(9)(10)(11). In general, these studies concluded that monitoring the ablation process utilizing real-time US was somewhat inaccurate, because the hyperechogenicity of the heated breast tissue and the ultrasonographic shadowing made it difficult to differentiate between ablated tissue and residual tumor (9,10).…”
mentioning
confidence: 99%
“…A total of 63 articles matched the selection criteria. The 63 articles included 16 feasibility studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], 12 phase I studies [29][30][31][32][33][34][35][36][37][38][39][40], nine phase II studies [41][42][43][44][45][46][47][48][49], three comparative studies [50][51][52], one retrospective study [53], and four randomised controlled trials [54][55][56]. In 18 studies the type of study was not reported [8,[57][58][59][60][61][62][63][64]…”
Section: Selected Studiesmentioning
confidence: 99%
“…Burak et al [15] treated tumours with a mean diameter of 12 mm, creating an ablation zone of 26-45 mm and reported one case with surviving malignancy. Viability was assessed using cytokeratin 8 ⁄ 18 stain.…”
Section: Radiofrequency Ablationmentioning
confidence: 99%